2022
DOI: 10.1055/a-1919-9558
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Issues in Women

Abstract: The lifetime risk of venous thromboembolism (VTE) is slightly higher in women than in men. There are several issues related to VTE that are unique to women. Combined hormonal contraceptives and pregnancy increase the risk of VTE in women of childbearing age, whereas hormone replacement therapy increases the VTE risk of postmenopausal women. Hereditary thrombophilia and risk factors such as older age, obesity, or smoking contribute to the risk increase. In women diagnosed with acute hormone-related VTE who are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Regarding the use of oral contraceptives , although pills currently have a lower concentration of estrogen, especially ethinyl estradiol, their use increases the risk of VTE by up to six times compared to those that do not use hormonally based contraceptives. The absolute risk, however, in women aged less than 35 years and without associated risk factors remains between low and moderate (Linnemann, et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the use of oral contraceptives , although pills currently have a lower concentration of estrogen, especially ethinyl estradiol, their use increases the risk of VTE by up to six times compared to those that do not use hormonally based contraceptives. The absolute risk, however, in women aged less than 35 years and without associated risk factors remains between low and moderate (Linnemann, et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the risk of venous thromboembolism (VTE) is higher in women than in men. Along with the use of combined oral contraceptives, pregnancy belongs to the clinical states increasing the risk of thromboembolic complications in women of childbearing age [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large epidemiological studies in various populations have shown increasing age, a family history of VTE, presence of acquired and inherited thrombophilia, COC use, pregnancy, and smoking to be independent risk factors for VTE, 8,9 and, in pregnant women, advanced maternal age, family history, caesarean section, multiparity, and multifetal pregnancies were found to be risk factors for pregnancy-associated VTE. 10,11 Ethnic differences have also been observed in risk factors and the incidence of pregnancy-associated VTE. 12 Other studies indicate that family history of VTE is an important risk factor for VTE in women who are pregnant or who are taking COC, irrespective of thrombophilia status.…”
mentioning
confidence: 99%